2023
DOI: 10.1007/s10729-023-09634-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of English hospitals during the first and second waves of the coronavirus pandemic

Abstract: The coronavirus infection COVID-19 killed millions of people around the world in 2019-2022. Hospitals were in the forefront in the battle against the pandemic. This paper proposes a novel approach to assess the effectiveness of hospitals in saving lives. We empirically estimate the production function of COVID-19 deaths among hospital inpatients, applying Heckman’s two-stage approach to correct for the bias caused by a large number of zero-valued observations. We subsequently assess performance of hospitals ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
0
1
Order By: Relevance
“…This hospital does not treat patients with COVID-19. This research is different from other studies that the authors have found, for example, similar research carried out in governmentowned hospitals and receiving COVID-19 patients (Wawo et al, 2020;Zeho et al, 2020), research that compares health care institutions in developed countries and developing countries during the COVID-19 pandemic (Wagdi & Abouzeid, 2021), studies that do not use the BSC method (Jalilian et al, 2023;Kuosmanen et al, 2023), and the research was not done during the COVID-19 pandemic (Setiawannie & Rahmania, 2019). The limitation of this study is that it only involved one private hospital, so it cannot represent all types of hospitals in Indonesia.…”
Section: Managerial Implicationscontrasting
confidence: 78%
“…This hospital does not treat patients with COVID-19. This research is different from other studies that the authors have found, for example, similar research carried out in governmentowned hospitals and receiving COVID-19 patients (Wawo et al, 2020;Zeho et al, 2020), research that compares health care institutions in developed countries and developing countries during the COVID-19 pandemic (Wagdi & Abouzeid, 2021), studies that do not use the BSC method (Jalilian et al, 2023;Kuosmanen et al, 2023), and the research was not done during the COVID-19 pandemic (Setiawannie & Rahmania, 2019). The limitation of this study is that it only involved one private hospital, so it cannot represent all types of hospitals in Indonesia.…”
Section: Managerial Implicationscontrasting
confidence: 78%